Bribing in Team Contests - Serhat Dogan; Emin Karagözoglu; Kerim Keskin; Cagri Saglam (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study bribing in a sequential team contest with multiple pairwise battles. We allow for asymmetries in winning prizes and marginal costs of effort; and we characterize the conditions under which (i) a player in a team is offered a bribe by the owner of the other team and (ii) she accepts the bribe. We show that these conditions depend on the ratios of players' winning prizes and marginal costs of effort: the team owner chooses to bribe the player with the most favorable winning prize to marginal cost of effort ratio, and offer a bribe that leaves her indifferent between accepting (and exerting zero effort) and not accepting (and exerting her optimal effort). In some cases, the competition between players and the negative consequences of one player receiving a bribe on the team performance can drag down equilibrium bribe to zero. We also study the impact of changes in winning prizes and marginal costs of effort on equilibrium bribing behavior.
Keywords: C72; D73; D74; 330; bribing; contest games; pairwise battles; team contests